2015
DOI: 10.1371/journal.pone.0144016
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Portuguese Lexicon: An Instrument for Psycholinguistic Research

Abstract: In this article, we present the Brazilian Portuguese Lexicon, a new word-based corpus for psycholinguistic and computational linguistic research in Brazilian Portuguese. We describe the corpus development, the specific characteristics on the internet site and database for user access. We also perform distributional analyses of the corpus and comparisons to other current databases. Our main objective was to provide a large, reliable, and useful word-based corpus with a dynamic, easy-to-use, and intuitive interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
(202 reference statements)
0
10
0
2
Order By: Relevance
“…The calculator had two parts: the database and the search engine (algorithm based on Vitevitch & Luce, 2004). The database was built from a comprehensive Brazilian-Portuguese corpus (Estivalet & Meunier, 2015) in five steps.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The calculator had two parts: the database and the search engine (algorithm based on Vitevitch & Luce, 2004). The database was built from a comprehensive Brazilian-Portuguese corpus (Estivalet & Meunier, 2015) in five steps.…”
Section: Stimulimentioning
confidence: 99%
“…To ensure that both sets were very similar to actual words from Brazilian-Portuguese, we calculated the mean number of insertions, deletions, and substitutions needed to transform PP+ and PP-words into their closest 20 phonetic neighbors (i.e., Levenshtein Distance; Yarkoni et al, 2008). We used the package vwr (Keuleers, 2013) for R (R Core Team, 2017) and the same Brazilian-Portuguese corpus in these calculations (Estivalet & Meunier, 2015; Table 1). The analysis indicated that both sets were very close to actual Brazilian-Portuguese words (1.26 for PP+, 1.52 for PP-; the smaller the number of operations, the closer the words were to Brazilian-Portuguese) and to each otherdifference of 0.26 mean operations.…”
Section: Stimulimentioning
confidence: 99%
“…Kettunen (2014) compares a number of European languages using different complexity metrics, particularly focusing on morphology, and finds that English (0.05) and EP (0.06) (and several other romance languages) are similar in their type–token ratios, as well as several other measures. Again, this analysis does not include BP, but other work provides type–token ratios for BP that are much lower (0.01) (Estivalet & Meunier, 2015), and given the large disparity (none of the languages included in the Kettunen study had values lower than 0.05), is likely to be explained by a different methodology for determining type–token ratio.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why this might be, and while there has been significant work on the salience of geographic features for wayfinding (e.g., Caduff & Timpf, 2008; Quesnot & Roche, 2015; Raubal & Winter, 2002), we are not aware of any cross‐linguistic studies that address the issue. Vocabulary studies show that the most frequently used word class in English is nouns (Kang & Yu, 2011; Tardif, Gelman, & Xu, 1999), whereas in BP verbs are used most frequently (Estivalet & Meunier, 2015), which might make English speakers more attuned to objects in their environment, but more studies are required to determine the cause of this variation in relata and locata selection frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Such databases have been created for several languages and are available in the form of a web application or computer software. Among them are the English lexicon project (Balota et al, 2007), eDom (Armstrong, Tokowicz, & Plaut, 2012), N-Watch (Davis, 2005) and MRC database (Coltheart, 1981) for English; DlexDB for German (Heister et al, 2011); Lexique (New, Pallier, Brysbaert, and Ferrand, 2004) for French; EsPal (Duchon, Perea, Sebastián-Gallés, Martí, & Carreiras, 2013) and BuscaPalabras (Davis & Perea, 2005) for Spanish; EHME (Acha, Laka, Landa, & Salaburu, 2014) and E-Hitz (Perea et al, 2006) for Basque; GreekLex (Ktori, van Heuven, & Pitchford, 2008) and GreekLex2 (Kyparissiadis et al, 2017) for Modern Greek; Aralex (Boudelaa & Marslen-Wilson, 2010) for Modern Standard Arabic; the Malay Lexicon Project (Yap, Liow, Jalil, & Faizal, 2010) for Malay; KelemetriK (Erten, Bozsahin, & Zeyrek, 2014) for Turkish; the Brazilian Portuguese Lexicon (Estivalet & Meunier, 2015) for Brazilian Portuguese, etc. All these databases are equipped with effective search and filtering tools.…”
Section: Introducing the Stimulstat Databasementioning
confidence: 99%